A violência no imaginário dos agentes educativos - Itani, Alice [UNESP] (Centro de Estudos Educação e Sociedade, 1998)
Violence is very much present in debates. In fact, it is part of school as social institution which is present in daily experience not only of educational agents but also of pupils, particularly in Brazilian society, with deep social inequality. How does violence develop in the practices and actions within the educational process? The notion of violence is commonly related to its most visible facet which is that of urban crime scenes and robberies. The dimensions through which violence manifests itself are diverse. Among the dimensions through which violence affects us most noxiously are those of legalized and institutionalized violence, which are very little visible, sometimes even invisible. For this reason, we are unable to defend ourselves against them. The action of educational agents is an institutionalized reaction, that could become institutionalized violence too, throughout the educational process which establishes and reproduces itself by dissemination throughout the social relationships. The present text seeks to contribute to the debate on the question of violence in schools by presenting some aspects observed in the actions and practices of educational agents and in daily school life.

A violência não é um tema novo na literatura e sempre suscita amplos debates. Na realidade, ela faz parte da escola como instituição social, estando presente na experiência cotidiana tanto dos agentes educativos como na dos alunos, notadamente pela profunda desigualdade social existente em alguns grupos sociais na sociedade brasileira. Como a violência se desenvolve nas práticas e ações no processo educacional? A noção de violência é comumente relacionada à sua faceta mais visível, a das cenas dos crimes urbanos e assaltos, amplamente exploradas e difundidas pela imprensa. Porém, várias são as formas pelas quais ela se realiza. Dentre estas, as mais nocivas abrigam-se na legalizada e institucionalizada, quase invisíveis aos olhos do cidadão, que não sabe se defender contra elas. A ação dos agentes educativos é uma violência institucionalizada. Mas é preciso distinguir duas ações: a que violenta os cidadãos pela reprodução da desigualdade, e a que socializa e impõe regras coletivas. A ausência da ação socializadora pode desdobrar-se em uma violência maior, pela falta de uma ética da vida. Este artigo busca contribuir para o debate sobre a questão da violência, apresentando alguns aspectos observados nas ações e práticas de agentes educativos e no cotidiano escolar.
Violence in the minds of the educational agents
Keywords: violência; imaginário; agentes educativos; educação; processo educativo